Nytt ventilationssystem till djurstallar - Pettersson, Anna (SLU/Dept. of Landscape Architecture, Planning and Management (from 130101), 2004)
There is two dairy farms in Sweden with ability to be opened on both long sides, one outside Hjo and the other one, Brandstadholm, north of Sjöbo. When there is no measures and results or not enough literature about natural ventilation and especially on this kind of air inlet, makes my tests very interesting not only on Alnarp, but among other companies. I would like to find out if there is any air movements direct on the cows, how high/low temperature, air humidity, light intensity and noise standard inside the barn. Does Brandstadholm fulfil the rules and regulations when it comes to climate inside the barn? Could this system become the new dairy barn instead of the conventional barns in Sweden? I am going to focus on the animals environment, after all they are the one who is going to spend the most of the time in the barn. I used five electrical loggers distributed inside the barn to measure the temperature and one of the loggers measured the air humidity, every 15th minute. One logger were placed on the outside which measured both temperature and air humidity. Every time I visited the farms I got some references on the loggers by measuring the temperature, air humidity and I also got some values on light, noise and air movements. Brandstadholm is partly an uninsulated and partly a isolated dairy barn. The dairy farm Brandstadholm, north of Sjöbo milk their 250 cows in a 30º angled fishbone pit (2x10) and there is three cubicle rows on each side of the feeding table. The roof has a regulated ridge opening which also is a light inlet. Both the roof and the gable is isolated while the long sides consist of double transparent plastic wall which is filled with air when the wall is closed. The air is blown in by fans and the wall can be opened in three steps. The first step is 30 cm from the eaves, step two is when the wall is half open and the last step is when fully open. The barn is natural ventilated. Bollerup is the referent dairy farm, 16 km northeast off Ystad and is Sweden's largest agricultural school. Just as Brandstadholm, Bollerup has three cubicle rows on each side of the feeding table. The school has two Lely milkingrobots and the barn has natural ventilation with an open ridge and a wall hatch as an air inlet together with space boarding on one gable. The roof is uninsulated and the walls consists of concrete from the eaves and down. When the day and night temperature is shifting too much and occurs too often the animals is affected by a negative thermal comfort. At a colder temperature the cows build fur to stay warm. Then the temperature rises and the cows begins to sweat on account of the fur which after a new temperature shift to a lower degree makes the cows freeze. Brandstadholm as mentioned before is partly isolated and is very comfortable to be in, compared with Bollerup. The results on the air humidity shows that the insulated roof are of importance when it keeps the barn warmer which holds the humidity down to a lower level as in Brandstadholm. Bollerups results are not bad if you compare to other uninsulated barns when the air humidity can be near 100 %. During my experiments, Bollerup has felt brighter than Brandstadholm. The results shows that it is so, but both dairy barns fulfil the rules and regulations. The noise standards in Bollerup is a borderline case which has to do with the two robots and the two automatic feeder together with the space boarding at strong wind. Brandstadholm on the other hand is very quiet. The wall hatch on the north side are the primarily air inlets together with the ridge in the west at Bollerup. The measures at Brandstadholm shows that there is not any air movements. There is not any air movements directly on the animals when the results I have found was under 1 m/s in both barns. The plastic wall can during a strong wind create unnecessary noise.